Technostress Pegawai Negeri Sipil Dinas Sosial Kabupaten Nagan Raya - Faulia, Firda; Muzakkir (Medan Resource Center, 2022)
Technostress is defined as the stress experienced by individuals due to their use of information systems and represents a phenomenon that examines how and why the use of information systems causes individuals to experience various demands that they find stressful. This research develops a framework for looking at the technostress experienced by individual civil servants at the Nagan Raya District Social Service. This research first reviews and critically analyzes the current state of research on technostress reported in journals from management disciplines studying stress in organizations (eg, organizational behavior and psychological stress). This study outlines 3 key ideas embodied in the existing technostress literature. First, it develops the argument that technostress can lead to positive outcomes such as greater effectiveness and innovation in the workplace. These two things show that instead of limiting the role of information systems technology to being a stressor in the technostress phenomenon this should be expanded to increase the positive effects and reduce the negative effects of technostress through proper design. These three matters lay the groundwork to guide future research in technostress through an interdisciplinary framework that enriches the human resources perspective of the psychological stress literature through discourse on potential disciplinary exchanges.